Developing a structured and strategically focused performance assessment system - Silva, J.; I. Almeida; Cabral, A.A. (Proceedings of 22nd EurOMA - Operations Management for Sustainable Competitiveness, 2015)
The number and adequateness of Performance Indicators (PIs) to organisational purpose are core to organisations success and a major concern of this research sponsor. This assignment developed a procedure to improve the performance assessment system of a firm, by identifying 2 Key PIs from 28 starting ones, by setting criteria and its relative importance to validate and rank the adequateness and the right number of operational metrics. Analytical Hierarchy Process was used together with a synthesis method to treat data coming from management inquiries. Despite the achieved organisational alignment, business processes should also be targeted and PIs continuously revised.